Rye and Triticale Breeding in the South - Ann R. Blount; Ron D. Barnett (EDIS)
This 2-page fact sheet is a minor revision written by A. R. Blount, R. D. Barnett, P. L. Pfahler, J. W. Johnson, G. D. Buntin, and B. M. Cunfer, and published by the Agronomy Department, January 2017.